Bacterial Contamination of a Phenolic Disinfectant. Issue 5658 (14th June 1969) - Simmons, N. A.; Gardner, D. A.
Abstract : Twenty ward stock bottles of aqueous 1% Printol were examined and 17 were found to be contaminated with Alcaligenes faecalis. Organisms were present in dead space behind the plastic liners of the bottle caps, where they could have survived washing. A. faecalis was also isolated from 31 out of 34 1% Printol solutions in use in the hospital. Pseudomonas aeruginosa was grown from two samples of 1% Printol in one ward, but not from stock bottles. The minimal bactericidal concentration (M.B.C.) in aqueous solution of Hycolin, Sudol, and Stericol for A. faecalis and Ps. aeruginosa was 1 in 320. The M.B.C. of Printol for both organisms was 1 in 80. The activity of all four disinfectants was reduced in the presence of large amounts of organic matter. Sudol was the least affected. Polyethylene, of which stock bottles were made, did not reduce the activity of the disinfectants. It is suggested that, ideally, stock bottles of disinfectant diluted ready for use should be autoclaved before they are refilled.